STRATEGI PENINGKATAN PENDAPATAN PETANI KELAPA SAWIT DI KECAMATAN LEUSER KABUPATEN ACEH TENGGARA - Jasa Ginting; Muhammad Buhari Sibuea; Rahmanta Ginting (JURNAL AGRICA, 2016)
The productivity of oil palm plantations in the district Leuser tends to decrease, this is not in line with the area's increasing crop yield. Decreased productivity impact on the incomes of farmers who have land transformation, this condition is certainly not expected of farmers. The purpose of this study to formulate appropriate strategies to improve the income of farmers in the district of palm Leuser Southeast Aceh district. By using SWOT analysis, the results showed that the resulting strategy is a strategy of business diversification of the diversity of both interrelated or not interrelated to increase farmers' income palm.Keywords: SWOT, Strategy Diversification, Farmers' Income